THE INFLUENCE OF PRODUCT QUALITY AND BRAND IMAGE ON THE PURCHASE DECISION OF MIXUE ICE CREAM AT THE BINTARA BRANCH IN WEST BEKASI - Rizki Dwi Ramadhani; Widi Winarso; Haryudi Anas (IJESM Indonesian Journal of Economics and Strategic Management, 2024)
Purpose – This study aims to measure the Effect of product quality and brand image on the purchase decision Mixue Ice Cream at Bintara Branch in West Bekasi.Design/methodology/approach – The sampling technique carried out in this study is based on the Slovin formula using Non-Prabobability Sampling. The data collection tool in this study used a questionnaire with 110 respondents.Findings – According to the report, Product Quality has a significant effect on Purchase Decision and Brand Image has a significant effect on Purchase Decision Mixue Ice Cream at Bintara Branch in West Bekasi. So the product quality and brand image of Mixue Ice Cream need to be maintained in order to increase purchasing decisions.Originality/value – Able to provide the best quality products according to consumer tastes and a good brand image so as to increase purchasing decisions.